2014
DOI: 10.1088/0029-5515/54/4/043001
|View full text |Cite
|
Sign up to set email alerts
|

Global and pedestal confinement in JET with a Be/W metallic wall

Abstract: Type I ELMy H-mode operation in JET with the ITER-like Be/W wall (JET-ILW) generally occurs at lower pedestal pressures compared to those with the full carbon wall (JET-C). The pedestal density is similar but the pedestal temperature where type I ELMs occur is reduced and below to the so-called critical type I–type III transition temperature reported in JET-C experiments. Furthermore, the confinement factor H98(y,2) in type I ELMy H-mode baseline plasmas is generally lower in JET-ILW compared to JET-C at low p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
151
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(168 citation statements)
references
References 38 publications
15
151
2
Order By: Relevance
“…However, the confinement in JET-ILW high triangularity baseline plasmas is reduced by 10 -30% over the entire fuelling range. In contrast to the situation in JET-C, the ELM frequency did not drop at higher puffing levels, but rather increased [57]. It has to be noted that the degraded confinement in the high triangularity pulses is not due to an increase in plasma radiation.…”
Section: B Plasma Confinementcontrasting
confidence: 60%
See 1 more Smart Citation
“…However, the confinement in JET-ILW high triangularity baseline plasmas is reduced by 10 -30% over the entire fuelling range. In contrast to the situation in JET-C, the ELM frequency did not drop at higher puffing levels, but rather increased [57]. It has to be noted that the degraded confinement in the high triangularity pulses is not due to an increase in plasma radiation.…”
Section: B Plasma Confinementcontrasting
confidence: 60%
“…4. In both devices the improved confinement with N seeding originates from an increased pedestal confinement [55], [57]. This suggests that the edge impurity composition has a strong effect on the pedestal stability and that nitrogen replaces carbon as a low-Z impurity.…”
Section: Impurity Seeding In High Power Operation In L-or H-modementioning
confidence: 89%
“…It is also to be underlined that the present work addresses multi-species collisions with no assumption regarding charge or mass. These are the basis for the collisional exchange between main species and impurities, an important issue in understanding and hopefully controlling present experiments with tungsten walls [11,12].…”
Section: Resultsmentioning
confidence: 99%
“…With the replacement of CW in JET by the ILW in 2010, it has been observed that the first wall material appears to have had an effect on both the plasma confinement and pedestal properties [20] [21]. Up until now, the JET-ILW standard baseline scenario has not routinely achieved a confinement factor of H 98 = 1 both in low and high-triangularity scenarios.…”
Section: Plasma Scenariomentioning
confidence: 99%